If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 21 = 10x + -10 Reorder the terms: 21 + 3x = 10x + -10 Reorder the terms: 21 + 3x = -10 + 10x Solving 21 + 3x = -10 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 21 + 3x + -10x = -10 + 10x + -10x Combine like terms: 3x + -10x = -7x 21 + -7x = -10 + 10x + -10x Combine like terms: 10x + -10x = 0 21 + -7x = -10 + 0 21 + -7x = -10 Add '-21' to each side of the equation. 21 + -21 + -7x = -10 + -21 Combine like terms: 21 + -21 = 0 0 + -7x = -10 + -21 -7x = -10 + -21 Combine like terms: -10 + -21 = -31 -7x = -31 Divide each side by '-7'. x = 4.428571429 Simplifying x = 4.428571429
| 3x-19=4x-19 | | x=2/12=5/x-2 | | 5j+7=72 | | 2/3 | | 90-2y=-4 | | 2(3x-4)=8x+4 | | 0=10x-25 | | 11x-4x+112=11x+80 | | -(7x-2)(7x-2)= | | 2u+12=16 | | d/dx=2cos3x | | 0.15-0.03(x+1)=-0.03(2-x) | | 284.18/20.99x93 | | 2x^2=15x-7 | | r+5.2=-0.3 | | (6x+-2y)-(2x+3y)= | | 3y=0+9 | | 9w+3=57 | | .07x+.23(60)=.15(60+x) | | 18x^8-7x^6+9x^5=0 | | 5k+12=22 | | 63y+10=5y-2 | | (6x+-2y)+(2x+3y)= | | 6x+7x-21=63-8x | | 0.39a=14.4 | | 4*57+48= | | 2-4.5x=-3x-13 | | 5a+8=43 | | 18ft+10in= | | 2w^2+9w-11=0 | | -0.2x-0.3x+6=1 | | .5(7x+48)= |